A Study of a Novel Synergy Definition for Ternary CB/CNT Composites Suggesting a Representative Model for CB and CNT - Yang, Guanda; Schubert, Dirk W.; Nilsson, Fritjof; Qu, Muchao; Redel, Michael (Macromolecular Theory and Simulations, 2020)
For polymer composites containing two types of conductive fillers, the electrical conductivity can be predicted with a ternary mixing equation. However, a slight deviation from the foreseen trend is recently observed for ternary polymethyl methacrylate (PMMA) nanocomposites containing carbon nanotubes (CNT) and carbon black (CB). In this study, the reason for the deviation is examined. Representative composite geometries are generated with Monte-Carlo technique and the composite conductivity is calculated with Finite Element Modeling (FEM) Traditional FEM strategies would give results resembling the ternary mixing equation, but when the CB particles are modeled as solid spheres whereas the CNT are modeled as solid cylinders surrounded by soft, conductive shells, the composite conductivity gained the same shape as observed experimentally. One possible interpretation is that a small geometrical rearrangement of the CNT fibers has a larger impact on the composite conductivity than a corresponding movement of the spherical CB particles. As a consequence, the CNT/CB/PMMA nanocomposite exhibits a special kind of synergy (“synergism”), caused by the grape-shaped morphology. These findings can be utilized in the future development and optimization of conductive polymer nanocomposites.
CRIS-Team Scopus Importer:2020-07-31
Keywords: conductivity; CPCs; simulation; ternary systems

Hierarchical Slice Patterns Inhibit Crack Propagation in Brittle Sheets - Zaiser, Michael; Hosseini, Seyyed Ahmad; Moretti, Paolo; Mäkinen, Tero; Koivisto, Juha; Poornajar, Mahshid; Himmler, Marcus; Redel, Michael; Schubert, Dirk W.; Alava, Mikko (Physical Review Applied, 2022)
By introducing hierarchical patterns of load-parallel cuts into axially loaded brittle sheets, the resistance to propagation of mode-I cracks is very significantly enhanced. We demonstrate this effect by simulation of two-dimensional beam network models and experimentally by testing paper and polystyrene (PS) sheets that are sliced with a laser cutter to induce load-perpendicular hierarchical cut patterns. Samples endowed with nonhierarchical reference patterns of the same cut density and nonsliced sheets are considered for comparison. We demonstrate that hierarchical slicing can increase failure load, apparent fracture toughness, and work of fracture of notched paper and PS sheets by factors between 2 and 10.<br

Impact of storage and processing on morphology in thermoplasic polyetherurethanes - Redel, Michael; Regelmann, Christian; Wölfel, Bastian; Schubert, Dirk W. (2023)
The presented study evaluates the influence of storage conditions as well as the impact of temperature, residence time, throughput and draw down speed in fibre spinning on the phase separation in commercially availa- ble thermoplastic polyether-urethanes. Many of the properties inherent to thermoplastic polyurethane (TPU) materials and products are due to the block-copolymer chain of soft and hard segments. The incompatibility of these segments causes demixing into so called “soft” and “hard phases” [1]. The degree of separation as well as the segment content are, according to literature, detectable via FTIR measurements [2]. Granules of two TPUs with differing compo- sition were stored for up to 900 days to eval- uate morphological changes and correlate to material shelf life. Samples consisting of varying ratios of MDI/BD hard and PTMG soft segments (Elastollan®) were subsequently processed by injection moulding. The hard segment ratio and the degree of microphase separation (DPS) were studied for all samples by analysing the peaks of ether and ure- thane groups as well as the free- and hydro- gen-bonded carbonyl (C=O) peaks, respec- tively. Hard segments feature a significantly higher density compared to soft segments, wherefore the results of the C-O peaks, cor- relating with the hard segment ratio, were validated. The determined DPS values were further related to the peak ratio of ether and urethane groups showing a linear correlation. In the second part, one TPU material was processed to nonwovens and characterized applying the calibrated FTIR method. The goal is to study the impact of the processing condi- tions during fibre spinning processes and to investigate the analytic capabilities for TPU

Model to Predict Polymer Fibre Diameter during Melt Spinning - Bier, Alexander; Redel, Michael; Schubert, Dirk W. (Advances in Polymer Technology, 2023)
Polymeric materials were evaluated with regard to their spinnability and respective fibre diameters. A modified single fibre spinning device was firstly used to derive a novel generalised model, utilising process parameters (die diameter, throughput, and stretching relevant take-up pressures) and material properties (zero shear viscosity) to predict the diameter of polymeric fibres on the basis of four different polymers. Further evaluation of the resulting power law dependence was conducted on filaments produced via conventional melt spinning and meltblown processes. Fibres produced on the pilot machines showed close agreement with the model equation with only the need to adjust an easily calculable device dependent factor. The outcome of the presented work is a user-friendly model of high practical relevance, which can be used to predict the diameter of amorphous and semicrystalline polymeric fibres, independent of material and machine used with sufficient accuracy for fast estimations.

Resonance phenomena in oscillatory shear rheometry: Influence of material parameters - Redel, Michael; Walter, Bastian; Kaschta, Joachim; Steinmann, Paul; Schubert, Dirk W. (Nordic Polymer Days 2018, 2018)
Rheological measurements are an established method for the characterisation of dynamic mechanical polymer properties. In current literature, possible restrictions to thesemeasurements by the phenomenon of resonance were evaluated by Stettin [1]. However, this paper is quiet about the influence of material parameters like stiffness or damping on the resonance phenomenon Therefore, an unfilled silicone elastomer, free of material particle interactions, is used. The cylindrical specimen are cured in a rheometer binding them firmly to the rotor. This has proven to prevent occurrence of for example wall slip [2]. The experiments conducted are frequency sweeps by means of a parallel-plate rheometer with a smooth geometry surface. Consequently, the influence of the setup, which was detected by Stettin [1], can be neglected. Resulting resonance frequencies are analysed concerning the material's damping and stiffness. Change in these parameters is realised by variation of mixture as well as addition of an additive. The resulting resonance frequencies show an explicit dependency of complex shear modulus |G*| as a measure of the stiffness. The resulting dependence in double logarithmic plot is compared with resonance frequency calculations based on oscillatory theories. Contribution of varying damping, realised by changing loss factor tan(δ), is detectable as an additional shift in resonance frequency and also discussed. Intriguingly, the wavedata of the stress response after resonance, obtained via fast Fourier transformation, differs from the expected sinusoidal signal. The change in wavedata and aberration from the sinusoidal excitation is explained by the phenomenon of vibration isolation. Furthermore, it is correlated with the material’s parameters reasoning the different experimental outcomes caused by the change in composition. A guideline to avoid the influence of resonance on oscillatory measurements is lastly presented